ANALISIS USAHA TANI BAWANG DAUN (Allium fistulusom L) DI DESA GONGSOL KECAMATAN MERDEKA KABUPATEN KARO - Gracia, Sarah; Sinaga, Roida Ervina (JURNAL AGROTEKNOSAINS, 2023)
The leek production center is Karo district, data on the planting area and harvest of leeks in Karo district in 2020 is 506 ha and a harvested area of 547 ha. for the average selling price of Rp. 5952/kg (Source: Central Bureau of Statistics 2020). Likewise with the data obtained from Merdeka District that the harvested area is 363 Ha with a production of 4433 tons with an average production of 12.12 ha/ton (Source: Central Statistics Agency 2020). Based on the description above, it can be concluded that Karo Regency is a source of leek commodity. And the biggest producer is in the village that produces spring onions, namely Gongsol Village, Merdeka District, Karo Regency, North Sumatra Province. Therefore, the researchers wanted to conduct research in Gongsol Village, with the title ANALYSIS OF LEAF GARNING BUSINESS (Allium Fistulusom L) in Gongsol Village, Merdeka District, Regency Karo.This study aims to analyze leek farming. The research was carried out in June - August 2023. Sampling used (Simple Random Sampling) and determining the number of respondents used the Slovin formula to obtain 30 respondent leek farmers. The research data used primary data obtained from interviews, questionnaires, and documentation with sample farmers in Gongsol Village, Merdeka District, Karo Regency. Analysis of data using the analysis of Feasibility Analysis of income farming, BEP Production, BEP Prices and analysis of R/C Ratio. nationally acrcredited journal : Quality University Agrotechnoscience journal.